2013
DOI: 10.3109/13816810.2013.867449
|View full text |Cite
|
Sign up to set email alerts
|

Association ofLOC387715/ARMS2(rs10490924) Gene Polymorphism with Age-Related Macular Degeneration in the Brazilian Population

Abstract: These results suggest that there is a contribution of the rs10490924 SNP of the LOC387715/ARMS2 gene to AMD susceptibility in this sample of the Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Previous studies have shown that the rs10490924 polymorphism, located in the ARMS2 gene, has a strong association with AMD (Rivera et al, 2005;Ross et al, 2007;Fritsche et al, 2008;Tong et al, 2010;Fuse et al, 2011;Soysal et al, 2012;Tamura et al, 2012;Hirata et al, 2013). Similar results were observed in our study through logistical regression analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that the rs10490924 polymorphism, located in the ARMS2 gene, has a strong association with AMD (Rivera et al, 2005;Ross et al, 2007;Fritsche et al, 2008;Tong et al, 2010;Fuse et al, 2011;Soysal et al, 2012;Tamura et al, 2012;Hirata et al, 2013). Similar results were observed in our study through logistical regression analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Rivera et al (2005) studied the same genetic region in 794 patients with AMD, and they reported a T allele frequency of 0.417. Hirata et al (2013) investigated the association between ARMS2 gene rs10490924 polymorphism and AMD. They found that the T allele frequency was significantly higher in patients with AMD than in the controls (39.6% compared to 20.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the genetic polymorphisms previously shown to be associated with risk for AMD [21][22][23][24][25][26][27][28][29][30][31][32][33][34], single nucleotide polymorphisms rs800292 (p = 0.0012), rs1410996 (p = 0.00019) and rs1061170 (p = 0.000064) within the complement factor H (CFH) gene and rs11200638 (p = 0.00012) within the high temperature requirement A serine peptidase 1 (HTRA1) gene were associated with a higher risk for having AMD in our cohort. However, rs12614 (p = 0.0057) within the complement factor B (CFB) gene was inversely correlated with AMD in the cohort (Fisher's exact test, Table 2).…”
Section: Association Between Single Nucleotide Polymorphisms and Amdmentioning
confidence: 99%
“…Research on genes related to AMD has been inconclusive because of the complexity of the disorder and involvement of multiple factors. Thus far, genes that have been reported to be associated with AMD include: ABCA4, CFH, EFEMP1, CFB, C2, RDS, VEGF, ELOVL4, CX3CR1, HTRA1, LOC387715, VMD2, APOE, and TIMP3 (Kanda et al, 2005;Klein et al, 2005;Gold et al, 2006;Fu et al, 2007;Leveziel et al, 2007;Spencer et al, 2007;Lin et al, 2008;Chen et al, 2012;Fritsche et al, 2012;Priya et al, 2012;Stanton et al, 2012;Sun et al, 2012;Hirata et al, 2013;Ersoy et al, 2014;Nazari Khanamiri et al, 2014). Although the involvement of some of some of these genes with AMD has been demonstrated in previous studies, conflicting results have also been reported.…”
Section: Introductionmentioning
confidence: 99%